(untitled) (Global Journal of Medical Research, 2014)
Amongst the list of pre-malignant conditions, Oral Submucous Fibrosis (OSMF) forms one of the most debilitating diseases of the oral cavity. It is predominantly seen among populations using betel quid, indicating areca nut as the most conspicuous agent in the etiological agents. A clear dosedependent relationship In relation to both the duration and frequency of chewing areca nut was revealed, although other risk factors such as excessive use of chilies and spices and malnutrition were also put forth. Research in some aspects in the background of progressive fibrosis associated with the disease, has allowed to put light onto the mechanisms involved in the malignant transformation to the most prevalent, potentially malignant oral disorder in south Asia. Reduction in matrix metalloproteinases (MMP’s) and increased secretion of tissue inhibitors of MMP’s play the most significant role in collagen accumulation whilst fibrogenic cytokines, mainly TGF-b over expression leading to increased production of collagen. There is increasing incidence of the disease and subsequent malignant transformation..